OP0037 First Pilot Study of An Implantable Loop Recorder (ILR) in Systemic Sclerosis Detects Significant Cardiac Arrhythmias with CMR Abnormalities. (15th July 2016) - Bissell, L.-A.; Dumitru, R.; Erhayiem, B.; Fent, G.; Greenwood, J.P.; Plein, S.; Andrews, J.; Graham, L.; Buch, M.H.
Abstract : Background: SSc-cardiomyopathy associated conduction abnormalities carry a poor prognosis, but their pathogenesis is unclear. Early detection to prevent complications is essential. ILRs are well-established in cardiology practice. Objectives: To determine the spectrum of cardiac conduction abnormalities (CCA) using the REVEAL® ILR & their association with CMR in patients (pts) with SSc with no known cardiac disease. Methods: 20 pts with (ACR/EULAR criteria) SSc, with no diabetes &/or more than 1 cardiovascular (CV) risk factor, were assessed for SSc/CV profile & comprehensive CV assessment performed, inc. 3T delayed enhancement-CMR (reported by CMR-cardiologists) & ILR insertion. ILR data was downloaded 3 monthly +/− at pt request if indicated. One yr data is reported. CMR compared to 30 healthy controls. Results: ILR data was available for 19 pts; 63% female, 84% Caucasian; mean (SD) age 53 (12)yrs, time from 1st non-RP symptom 9 (8)yrs; 32% dcSSc, 32% ACA+ve, 21% Scl70+ve, 54% palpitations hx, 42% known ILD, 11% DU hx, 0% pulmonary hypertension. Ten (52%) pts had ILR abnormalities; 4 with dcSSc, 3 ACA+ve, 3 Scl70+ve, 6 with palpitations hx, 4 known ILD, 3 DU hx. Subanalysis; 8 (42%) pts had supraventricular ectopics (SVE), 2 (11%) with ventricular ectopics (VE), 4 (21%) with arrhythmias of which 1 atrial flutter, 1 SVT, 1 VT & 1 complete heart block (CHB). Of the 4 pts with arrhythmias; 2 had dcSSc, 1 ACA+ve, 1 Scl70, 3 palpitations hx, 2 known ILD, 2 DU hx. Pt with CHB (dcSSc) had few SVE/VEs & 3 couplets on 24hr ECG 6 weeks previous. CMR data was available for 15 SSc pts (DE in 14; 1 pt claustrophobic, no IV access in 2, 1 CMR abandoned due to pacemaker insertion for CHB). Trend towards lower LVmass & distensibility (ie greater arterial stiffness) & higher extracellular volume (ECV, fibrosis marker) seen in pts with ILR abnormalities (p>0.05). Trend for higher ECV in those with SVE [unadj. mean difference (diff.) (95%CI) 1.1 (-2.5, 4.7)% p0.513], VE [0.7 (-4.9, 6.3)% p0.789] & arrhythmias [1.8 (-3.7, 7.3)% p0.486]. ECV was higher in SSc vs. controls; mean diff. 4.9 (3.2, 6.6)% p<0.001 R 2 0.568, adj. for age/sex; with trend for lower LV mass & distensibility. Conclusions: This first ILR in SSc study demonstrates its utility in the incidental detection of CCA, including serious cardiac arrhythmias & suggests associated CMR abnormalities. These data support the need for identification of pts at risk that would benefit from ILR & provide insights into the pathogenesis of SSc-cardiomyopathy Disclosure of Interest: None declared